2020
DOI: 10.1111/pin.13041
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of amyloidosis subtypes based on tissue biopsy site − Consecutive analysis of 729 patients at a single amyloidosis center in Japan

Abstract: This study was performed to elucidate the distribution of amyloidosis subtypes based on tissue biopsy site. Samples obtained from 729 consecutive patients with amyloidosis were analyzed by immunohistochemical staining (IHC) and supplemental mass spectrometry (MS). The correlations between the type of organs from which samples were obtained and amyloidosis subtypes were investigated retrospectively. Among the patients, 95.1% were diagnosed by IHC and 4.9% were diagnosed by MS. The distribution of amyloidosis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Immunohistochemistry analysis using AH1 and AH2 antibodies was performed on tissue samples obtained by biopsy or autopsy of 11 patients with AH amyloidosis, including 1 unreported patient 8–10,14,18 . The diagnosis of AH amyloidosis was confirmed by amino acid sequence analysis or LMD/MS analysis performed at Shinshu University, Japan 18 . IHC studies using anti‐λlight chain, anti‐κlight chain, anti‐amyloid A (AA), and anti‐transthyretin (TTR) antisera 18 revealed that 11 patients were negative for these proteins.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Immunohistochemistry analysis using AH1 and AH2 antibodies was performed on tissue samples obtained by biopsy or autopsy of 11 patients with AH amyloidosis, including 1 unreported patient 8–10,14,18 . The diagnosis of AH amyloidosis was confirmed by amino acid sequence analysis or LMD/MS analysis performed at Shinshu University, Japan 18 . IHC studies using anti‐λlight chain, anti‐κlight chain, anti‐amyloid A (AA), and anti‐transthyretin (TTR) antisera 18 revealed that 11 patients were negative for these proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of AH amyloidosis was confirmed by amino acid sequence analysis or LMD/MS analysis performed at Shinshu University, Japan 18 . IHC studies using anti‐λlight chain, anti‐κlight chain, anti‐amyloid A (AA), and anti‐transthyretin (TTR) antisera 18 revealed that 11 patients were negative for these proteins. The clinical information and biochemical data for the amyloid fibril proteins in these patients are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations